Taxing dividends in a dual income tax system: The Nordic experience with the income splitting rules - Håkan Selin (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2024)
In a dual income tax (DIT) system, labor income is taxed progressively, while capital income is subject to a lower proportional tax. DIT systems were introduced in Sweden, Norway, and Finland in the early 1990s. In the absence of rules restricting capital income distributions, owners of closelyheld corporations would easily be able to circumvent the progressive tax on earned income by withdrawing an appropriate amount of dividends instead of wages. The Nordic countries adopted very different income splitting models, with immediate implications for the tax treatment of dividends. In this article I first review the p rinciples o f the income splitting rules of Sweden, Norway, and Finland. I then discuss some of the tradeoffs involved in the design of such rules.
Keywords: H32; G35; 330; Income taxation; Nordic comparison; dividend taxation